The effect of subarachnoid or epidural bupivacaine on the QTc and P-wave dispersion - Seçen, Özlem; Ozcan, Sibel; Altun, Aysun Yıldız; Demırel, Ismail (My University, 2020)
Aim: Bupivacaine, which is widely used in neuraxial anesthesia, may lead to negative inotropic effect and arrhythmias. In this study,our objective is to evaluate the effects of bupivacaine on corrected QT interval (QTc) and P wave dispersion in epidural anesthesiaand to compare them with those in spinal anesthesia.Material and Methods: Ninety patients (59 male, 31 female) who applied neuraxial anesthesia for unilateral inguinal herniarepair were randomly allocated into two groups: Group S (Spinal, n = 49), Group E (Epidural, n = 41). Neuraxial anesthesia wasperformed by bupivacaine in both groups. We calculated heart rate, QT interval, corrected QT interval and P wave dispersion fromelectrocardiography, before anesthesia and after the operation.Results: Postoperative QT interval was significantly longer than preoperative value in both groups (preoperative 0.388 sec in GroupS and Group E versus, postoperative 0.407 sec in Group S and 0.397 sec in Group E), (p=0.001). Postoperative QTc prolongationwas significantly higher in Group S, but there was no statistically significant difference between the groups (preoperative 0.418sec versus, postoperative 0.424 sec in Group S), (p = 0.129). Preoperative and postoperative P wave dispersion value revealed nostatistically significant differences in both inter- and intragroup comparisons.Conclusion: Bupivacaine caused a postoperative QTc interval prolongation in spinal and epidural anesthesia, which did not reachlevels that were regarded as risky for ventricular arrhythmias despite being more prominent in the spinal anesthesia group comparedwith the epidural anesthesia group.
Keywords: Anestezi